2022
DOI: 10.1038/s41467-022-35046-2
|View full text |Cite
|
Sign up to set email alerts
|

Energy cascades in donor-acceptor exciton-polaritons observed by ultrafast two-dimensional white-light spectroscopy

Abstract: Exciton-polaritons are hybrid states formed when molecular excitons are strongly coupled to photons trapped in an optical cavity. These systems exhibit many interesting, but not fully understood, phenomena. Here, we utilize ultrafast two-dimensional white-light spectroscopy to study donor-acceptor microcavities made from two different layers of semiconducting carbon nanotubes. We observe the delayed growth of a cross peak between the upper- and lower-polariton bands that is oftentimes obscured by Rabi contract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Figure presents the results of a single-walled carbon nanotube (SWCNT) system (∼1000 atoms) coupled to an optical cavity, which has been the subject of recent experimental interest in molecule–cavity coupling. Semiconducting SWCNTs are known to have weak photoluminescence due to low-lying optically inactive states below the so-called band-edge E 11 exciton, which is the 6th excited state, and we denote |ψ 6 ⟩ ≡ | E 11 ⟩. Figure a provides the transition dipole matrix for the pristine (6,5) SWCNT system, showing a sparse matrix with only the ground-to-E 11 (i.e., the sixth bare molecular transition) transition to be optically allowed with a large dipole moment of ∼28 au, and small dipole matrix elements between other excited states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure presents the results of a single-walled carbon nanotube (SWCNT) system (∼1000 atoms) coupled to an optical cavity, which has been the subject of recent experimental interest in molecule–cavity coupling. Semiconducting SWCNTs are known to have weak photoluminescence due to low-lying optically inactive states below the so-called band-edge E 11 exciton, which is the 6th excited state, and we denote |ψ 6 ⟩ ≡ | E 11 ⟩. Figure a provides the transition dipole matrix for the pristine (6,5) SWCNT system, showing a sparse matrix with only the ground-to-E 11 (i.e., the sixth bare molecular transition) transition to be optically allowed with a large dipole moment of ∼28 au, and small dipole matrix elements between other excited states.…”
mentioning
confidence: 99%
“…Finally, we applied the pQED scheme to investigate the polaritonic properties of a single-walled carbon nanotube, a system of recent experimental interest for polaritonic applications. ,,,,,, We showed that through light–matter coupling one can red-shift the bright E 11 character of the tube below the band of dark states (which makes these materials dark to emission outside the cavity), thus enabling strong optical emission from these materials inside the cavity without the need for chemical functionalization.…”
mentioning
confidence: 99%
“…These spectroscopic experiments are key to examining and explaining a great many things related to excited nonradiative dynamics, even for defect-free systems, relevant to transient 55 57 and other nonlinear spectroscopies. 58 Upon the introduction of local defects, these experiments probe processes such as exciton trapping/detrapping events at these trapping sites 33 or exciton–polariton dynamics involving defect states. 16 …”
mentioning
confidence: 99%
“…For example, resonant Raman spectroscopy for pristine and functionalized SWCNTs has been reported but not well-decomposed and interpreted in the context of functionalization beyond the famous and prominent active modes in graphene and SWCNT systems, namely, the defect-associated mode (D), the graphene-like mode (G), and the radial breathing mode (RBM). These spectroscopic experiments are key to examining and explaining a great many things related to excited nonradiative dynamics, even for defect-free systems, relevant to transient and other nonlinear spectroscopies . Upon the introduction of local defects, these experiments probe processes such as exciton trapping/detrapping events at these trapping sites or exciton–polariton dynamics involving defect states …”
mentioning
confidence: 99%
“…In the out-of-plane cavity direction (i.e., perpendicular to the mirrors), these states are delocalised over the molecules inside the mode volume, while in the in-plane direction (i.e., parallel to the mirrors) they behave as quasi-particles with a low effective mass and large group velocity (i.e., fractions of the speed of light). These polaritonic properties can be exploited for both out-of-plane [9][10][11][23][24][25][26][27][28][29][30], and in-plane energy transport [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Indeed, at cryogenic temperatures in-plane ballistic propagation at the group velocity of polaritons was observed for polariton wavepackets in a Fabry-Pérot microcavity containing an In 0.05 Ga 0.95 As quantum well [31].…”
Section: Introductionmentioning
confidence: 99%